6x+5y=-9

Subtract 5y from both sides of the equation.

6x=-9-5y

Divide each term in 6x=-9-5y by 6.

6×6=-96+-5y6

Cancel the common factor of 6.

Cancel the common factor.

6×6=-96+-5y6

Divide x by 1.

x=-96+-5y6

x=-96+-5y6

Simplify each term.

Cancel the common factor of -9 and 6.

Factor 3 out of -9.

x=3(-3)6+-5y6

Cancel the common factors.

Factor 3 out of 6.

x=3⋅-33⋅2+-5y6

Cancel the common factor.

x=3⋅-33⋅2+-5y6

Rewrite the expression.

x=-32+-5y6

x=-32+-5y6

x=-32+-5y6

Move the negative in front of the fraction.

x=-32+-5y6

Move the negative in front of the fraction.

x=-32-5y6

x=-32-5y6

x=-32-5y6

Solve for x 6x+5y=-9